જો $x \ne 0 $ તો ${\left( {{{{x^l}} \over {{x^m}}}} \right)^{({l^2} + lm + {m^2})}}$${\left( {{{{x^m}} \over {{x^n}}}} \right)^{({m^2} + nm + {n^2})}}{\left( {{{{x^n}} \over {{x^l}}}} \right)^{({n^2} + nl + {l^2})}}=$
$1$
$x$
અસ્તિત્વ નથી
એકપણ નહીં
$\sqrt {[12 - \sqrt {(68 + 48\sqrt 2 )} ]} = $
${{{{2.3}^{n + 1}} + {{7.3}^{n - 1}}} \over {{3^{n + 2}} - 2{{(1/3)}^{l - n}}}} = $
જો ${a^{x - 1}} = bc,{b^{y - 1}} = ca,{c^{z - 1}} = ab,$ તો $\sum {(1/x) = } $
સમીકરણ ${(x)^{x\sqrt x }} = {(x\sqrt x )^x}$ ના ઉકેલની સંખ્યા મેળવો.
$\sqrt {(3 + \sqrt 5 )} = . .$ .